Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.4049/jimmunol.175.2.1100
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role for the Oligoadenylate Synthetase/RNase L Pathway in Response to IFN-β during Acute Ocular Herpes Simplex Virus Type 1 Infection

Abstract: We previously demonstrated that IFN-β transgene treatment protects mouse trigeminal ganglia (TG) cells from acute HSV-1 infection in vitro. However, IFN-α6 transgene treatment does not provide protection against acute HSV-1 infection in vitro, even though equivalent levels of IFN are expressed with both transgene treatments. In the present study we show that IFN-β transgene treatment before acute ocular HSV-1 infection protects mice from HSV-1-mediated mortality, whereas IFN-α6 transgene treatment does not red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 46 publications
2
50
1
Order By: Relevance
“…Yet, in the absence of CD118, the antiviral efficacy of the Ad:IFN-␥ was not lost. It was anticipated the effectiveness of Ad:IFN-␥ would not require antiviral pathways including OAS and PKR pathways implicated in the inhibition of HSV-1 (16,17,39,42,43). In contrast to previous observations in vitro (15), effectiveness of IFN-␥ transgene was lost in vivo in the absence of intact OAS or PKR signaling.…”
Section: Discussioncontrasting
confidence: 54%
“…Yet, in the absence of CD118, the antiviral efficacy of the Ad:IFN-␥ was not lost. It was anticipated the effectiveness of Ad:IFN-␥ would not require antiviral pathways including OAS and PKR pathways implicated in the inhibition of HSV-1 (16,17,39,42,43). In contrast to previous observations in vitro (15), effectiveness of IFN-␥ transgene was lost in vivo in the absence of intact OAS or PKR signaling.…”
Section: Discussioncontrasting
confidence: 54%
“…In addition, it has been shown that RNase L is activated in West Nile virus-infected cells and plays a role in the cellular antiviral response to flaviviruses [64]. The RNase L pathway has also been implicated in the response to IFN-beta during acute ocular herpes simplex virus type 1 infection (HSV-1) of mouse trigeminal-ganglia (TG) cells [65]. a) Mechanism of action-A localized model of activation of RNase L could lead to preferential degradation of viral vs. cellular RNA.…”
Section: Iii) Biological Activities Of Rnase L 1) Antiviral Activitymentioning
confidence: 99%
“…Evidence of this includes studies in the Friend retrovirus (FV) model, which showed that treatment with distinct IFN-␣ subtypes induced specific downstream responses that effectively controlled FV infections, whereas other subtypes induced responses that were ineffective (7,8). Furthermore, murine herpesvirus or influenza virus infections were controlled by different subtypes than those inhibiting FV (9)(10)(11)(12)(13). Recent in vitro work demonstrated not only differential relative expression of IFN-␣ subtypes in human plasmacytoid dendritic cells (pDCs) after human immunodeficiency virus type 1 (HIV-1) exposure, but also variable HIV-1 antiviral potencies of IFN-␣ subtypes in gut lamina propria mononuclear cell (LPMC) cultures (14).…”
mentioning
confidence: 99%